PENGELOLAAN FASILITAS OBJEK WISATA AKA BARAYUN LEMBAH HARAU BERBASIS MASYARAKAT DI KABUPATEN LIMA PULUH KOTA - Sastra, Zony Sastra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine Attractions Facilities Management Barayun Aka Harau Valley Community Based Fifty Cities in the District.This research uses descriptive quantitative method to examine the issue in the lift. The samples in this study were 100 respondents, taken using accidental sampling. While data collection techniques in this research using questionnaires, observation, and documentation. By using a Likert scale as a measure to determine the length of the short interval.Based on the research that has been conducted, the results of which may be that the Facilities Management attractions Barayun Aka Harau Valley Community Based Fifty Cities in the District. Included in both categories, as in the Aka Barayun Valley Attractions Harau which manages the trimmings is the local community.Keywords: Management, Facilities, Attractions, Harau Valley, Aka Barayun,district Fifty Cities